2004
DOI: 10.1007/s00204-003-0539-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between biomarkers of polycyclic aromatic hydrocarbon exposure and electrophilic tissue burden in a rat model

Abstract: This study was aimed at investigating the correlation between biomarkers of exposure to polycyclic aromatic hydrocarbons and, more specifically, at examining the role of urinary 1-hydroxypyrene (1-OHP) as a reliable measure of internal dose linked to the electrophilic tissue burden (ETB), assessed as covalent binding of the ultimate carcinogen benzo( a)pyrene diolepoxide (BaPDE) with cellular proteins in target organs. The protocol included experimental verification of a previously proposed algorithm for adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A common pitfall for estimating PAH toxicity is the erratic variations of environmental mixtures and the many possible biotransformation pathways for PAHs in organisms. Toxicity could result from receptor competition, impaired cellular uptake, protein binding, impaired cellular functions, disrupted intercellular communications, mutations, among others . Binary mixture data are a necessary first step in elucidating interactions in complex mixtures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common pitfall for estimating PAH toxicity is the erratic variations of environmental mixtures and the many possible biotransformation pathways for PAHs in organisms. Toxicity could result from receptor competition, impaired cellular uptake, protein binding, impaired cellular functions, disrupted intercellular communications, mutations, among others . Binary mixture data are a necessary first step in elucidating interactions in complex mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity could result from receptor competition, impaired cellular uptake, protein binding, impaired cellular functions, disrupted intercellular communications, mutations, among others. (14,16,40) Binary mixture data are a necessary first step in elucidating interactions in complex mixtures. More complex mixtures, such as ternary or quaternary, can further improve current knowledge on complex interactions.…”
Section: Mixturesmentioning
confidence: 99%
“…Many PAH are carcinogenic and mutagenic. Benzo[a]pyrene undergoes metabolism by CYP1A1 to epoxides which are further metabolized by epoxide hydrolases to dihydrodiols which can be further activated to the highly carcinogenic benzo(a)pyrene-7,8-dihydrodiol-9,10-epoxide ( Figure 1) (17,(53)(54)(55)(56)(57)(58)(59)(60). Of the four possible diol epoxides, (+)-(7R,8S,9S,10S) diol epoxide-2 was found to be the most potent carcinogen.…”
Section: Introduction Tobacco Exposure and Pregnancymentioning
confidence: 99%
“…A moderate correlation was reported between free NNAL and N 7 -MEG in a group of urothelial carcinoma patients split between smokers and non-smokers (Lee et al, 2008). BPDE-haemoglobin adducts but not the albumin adduct were highly correlated with the urinary polyaromatic hydrocarbon 1-hydroxypyrene (Tzekova et al, 2004). Interestingly another study conducted with smokers and non-smokers reported no correlation between the BPDE–haemoglobin adduct and cotinine whilst a moderate correlation was reported between the BPDE–albumin adduct and cotinine (Pastorelli et al, 2000; Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%